Partisipasi Masyarakat Kelurahan Jelakombo terhadap Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Skala Mikro Di Kabupaten Jombang - Ertien Rining Nawangsari; Ardha Wildan Rahmadani; Nosa Yudha Firmansyah; Yovi Arif Zachary (Jurnal Syntax Transformation, 2021)
The Covid-19 outbreak has spread rapidly throughout the world, including in Indonesia. In this case the government is taking steps towards public policies such as Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) to stop the spread of this virus. In deciding on its spread, the government needs public participation. Kelurahan Jelakombo participated in breaking the chain of spreading this virus. The purpose of this scientific article is to determine the form of public participation in implementing public policies designed to cut the spread of the virus. The method used is descriptive qualitative data collection in the form of interviews and direct observation. The theory used in this article is Community Participation by Mardikanto & Soebianto which describes the forms of participation divided into four forms, starting with the planning, implementation, evaluation and utilization of results. The results of this study are that community participation in Jelakombo Village has been involved in the planning, implementation, benefit involvement and evaluation stages of Community Activity Restriction (PPKM) to prevent Covid-19 transmission. The people of Jelakombo Village have followed the policy of Restricting Community Activities (PPKM) well, because the positive number of Covid-19 in Jelakombo Village from March 2020 to March 2021 was only 27 cases.